ADAB BERPAKAIAN MUSLIM DAN MUSLIMAH DALAM FIQIH - Imam Tauhid; Aulia Fathonah; Atik Rohmaniyati; Juwita Iqlima; Riska Firdhi Cahyan (Al Arsy: Journal of Education, Management and Islamic Thought, 2025)
Muslim brotherhood and maintaining silaturahmi are fundamental concepts in Islam that aim to strengthen social relations among Muslims and support the creation of a harmonious and civilized society. This article aims to examine the meaning of ukhuwah Islamiyah as a spiritual bond that binds fellow Muslims and examines the importance of silaturahmi as a practical manifestation of ukhuwah. A qualitative literature review method was used to gather information from various Islamic literature sources, the Qur'an, and Hadith. The results of the study indicate that ukhuwah as a theoretical concept must be realized through consistent silaturahmi so that brotherhood among Muslims can be maintained and developed. Maintaining silaturahmi not only brings blessings and rewards but also maintains the unity and harmony of the Muslim community. This article emphasizes that ukhuwah and silaturahmi are two complementary concepts in building a united and harmonious Muslim community.